2015
DOI: 10.1179/1743284714y.0000000691
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence of tetragonality in bainitic ferrite

Abstract: There is growing evidence that bainitic ferrite which retains a substantial amount of carbon in solid solution does not have cubic symmetry. We provide additional data on a different nanostructured bainitic steel to support this evidence, based on synchrotron X-ray diffraction experiments. The data are consistent only with a displacive transformation mechanism for bainite.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 17 publications
3
25
1
Order By: Relevance
“…[38] More recently, the possibility has been investigated using density functional calculations that tetragonality of the bainitic ferrite may also act to stabilize the high carbon content. [39] This is the topic of continuing investigations using synchrotron radiation [40,41] and neutron diffraction.…”
Section: Resultsmentioning
confidence: 99%
“…[38] More recently, the possibility has been investigated using density functional calculations that tetragonality of the bainitic ferrite may also act to stabilize the high carbon content. [39] This is the topic of continuing investigations using synchrotron radiation [40,41] and neutron diffraction.…”
Section: Resultsmentioning
confidence: 99%
“…59,61 There is also the contribution of the dislocation density and that of the Cottrell atmospheres, 59,62,63 as well as an important strengthening due to the solid solution of C in both ferrite and austenite. 64 The fact that nanostructured bainitic ferrite is tetragonal 30,38,52,65,66 allows it to accommodate a bigger amount of C in solid solution, 0.18 wt.%, when compared with the cubic structure. Therefore, its contribution to strength must be not inconsiderable.…”
Section: Nanostructure In Low-temperature Bainitic Steelmentioning
confidence: 99%
“…In a similar manner and given the recent findings, the lattice parameter of bainitic ferrite was calculated assuming that in these nanostructured bainitic steels, this phase has a tetragonal structure. 38,39 Thus, the C content of bainitic ferrite (X a ) was calculated as function of the tetragonal lattice parameters, a a and c a , according to the wellknown expression c a /a a = 1 + 0.045X a . 30,40,41 Further details on the setting of the XRD experiments and data treatment can be found in Ref.…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%
“…Fe-1.037C-3.89Si-1.97Mn-0.24Mo-1.43Al (wt-%) 54 have also shown a better fit obtained for the data of the BF lattice when lattice tetragonality is assumed. Anisotropy in thermal expansion along unit cell edges of BF during in situ synchrotron studies was also reported recently.…”
Section: Carbon and Lattice Tetragonalitymentioning
confidence: 73%